A8.12 AAV mediated expression of CD39 and CD73 is effective in reducing inflammation in the air pouch synovial inflammation model. (13th February 2015) - Finn, JD; Snoek, S; van Ittersum, J; Broekstra, N; Braam, C; Kramer, E; van Geldorp, M; Tak, PP; Vervoordeldonk, MJ
Abstract : Background and objectives: The conversion of extracellular ATP (eATP) to adenosine is an important mechanism of immune suppression through the coordinated activity of two enzymes, CD39 and CD73. CD39 is a membrane bound ATPase, and CD73 is a membrane bound ectonucleotidase that converts AMP to adenosine. We have previously presented evidence that the balance between pro-inflammatory eATP and anti-inflammatory adenosine is skewed in the synovial compartment of rheumatoid arthritis patients. Here we investigated the efficacy of Adeno-associated viral type 5 (AAV5) vector mediated expression of CD39 and CD73 on in vitro and in vivo inflammation models. Materials and methods: Adeno-associated viral (AAV) vectors expressing CD39 or CD73 were generated and used to transduce HEK 293 cells or RA fibroblast-like synoviocytes (FLS) and these transduced cells were co-cultured with LPS-activated human monocytes (THP-1) in the presence of ATP. Pro-inflammatory cytokine/chemokine (IL-6, CCL2) production was measured by ELISA. In vivo efficacy of AAV5-CD39-CD73 was investigated using the air pouch synovial inflammation (APSI) model in Balb/c mice using LPS as inflammatory stimulus. Pro-inflammatory cytokines (CCL2, IL-6) were measured by ELISA. Results: HEK 293 cells and RA FLS cell lines transduced with CD39-and/or CD73-expressing AAV5 vectors demonstrated high CD39 and CD73 activity. THP-1 cells stimulated with LPS showed lower levels (>80% reduction p = <0.05) of IL-6 and CCL2 secretion when co-cultured with CD39 and CD73 expressing HEK293 cells or FLS cells in the presence of ATP. AAV mediated expression of CD39 and CD73 in the air pouch membrane resulted in significant decreases in pro-inflammatory cytokine levels at 24 h (˜35% reduced CCL2 p < 0.05) and 48 h (25% reduced CCL2 levels p < 0.05, 80% reduced IL-6 levels p < 0.001) post LPS administration. Conclusion: Together, these data suggest that AAV mediated expression of CD39 and CD73 may be a novel strategy for the treatment of inflammatory disease, including RA.